1951
DOI: 10.1149/1.2778138
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism and Rate of Dissolution of Titanium in Hydrofluoric Acid

Abstract: Titanium dissolves rapidly in hydrofluoric acid according to the reaction: 2normalTi+6HF→2TiF3+3H2 . The formation of the trifluoride was confirmed by titration with potassium permanganate solution and by measurement of the volume of hydrogen evolved. The rate of dissolution, V , of titanium in hydrofluoric acid of concentrations between 0.02N and 0.2N conforms with the empirical equation: V=459N2/3 mm3/cm2min . For the acid between 0.2N and 10N the equation becomes V=88+473N mm3/cm2min . Metal salts added… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1955
1955
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…Therefore, in the TiO 2 –HF–H 2 O system, Ti was rapidly attacked and underwent corrosion and erosion. Ti fluorides such as soluble Ti trifluoride (TiF 3 ), Ti tetrafluoride (TiF 4 ) (Straumanis & Chen, 1951), and Ti oxyfluoride (TiOF 2 ) (Busalev et al, 1962) were formed. In the present study, high-resolution ESEM observations in both the body and apex regions showed a nanolevel surface topography with micro- and nano-rounded coarseness (flakes and micropits) spaced out with porosities and depressions consistent with the acid treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in the TiO 2 –HF–H 2 O system, Ti was rapidly attacked and underwent corrosion and erosion. Ti fluorides such as soluble Ti trifluoride (TiF 3 ), Ti tetrafluoride (TiF 4 ) (Straumanis & Chen, 1951), and Ti oxyfluoride (TiOF 2 ) (Busalev et al, 1962) were formed. In the present study, high-resolution ESEM observations in both the body and apex regions showed a nanolevel surface topography with micro- and nano-rounded coarseness (flakes and micropits) spaced out with porosities and depressions consistent with the acid treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Journal of The Electrochemical Society, 162 (9) H604-H610 (2015) model EIS data at OCP [2] where k 2 and k 4 are independent of potential. Later, the dissolution in transpassive region (5 V vs. SCE) is modeled using kinetic mechanism proposed below…”
Section: H608mentioning
confidence: 99%
“…The properties of the passivation layer, such as thickness, depend largely on the current density/electrode potential applied, the electrolyte composition and, of course, the duration of the polarisation [21]. The stability of the oxide layer is greatly reduced by the presence of fluorides in an acidic environment [24], in fact hydrofluoric acid is practically the only acid that dissolves Ti even in diluted solutions [26,27]. The rate of Ti dissolution in halogen hydride acid decreases with increasing atomic mass of the halogen [26].…”
Section: Introductionmentioning
confidence: 99%